1968
DOI: 10.1002/ar.1091610108
|View full text |Cite
|
Sign up to set email alerts
|

The fine structure of sow lutein cells

Abstract: The morphological observations described in this reuort are part of a biochemical study of progesterone intermediates using sow ovary. This tissue is extensively involved in the production of some steroid hormones. Because the lutein cells are thought to be involved in the synthesis of progesterone and its intermediates and because these cells constitute by size and number the greatest portion of the mass of sow ovary, we confined the morphological investigation to these cells. Sow corpora lutea, fixed with gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1969
1969
1982
1982

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“….. 277 terized by their content of abundant agranular endoplasm ic reti culum, lipid droplets, m itochondria with tubular cristae, dense bodies, and Golgi apparatus, i.e., similar to cells involved in the production of steroid hormones. Recently, correlated morphological and biochemical studies have shown th at the m em branes of the agranular endoplasmic reticulum (or diffuse lipoproteins) play large roles as sites for enzymes involved in steroidogenesis [see Christen sen , 1965;Christensen and Fawcett, 1966;Goodman et al, 1968;G uraya, 1968a,b,c, 1969aFawcett etal., 1969;Christensen and Gillim, 19691; the Leydig cells of the mouse testis, which contain abundant diffuse lipoproteins (figs.25, 26), also show abundant m em branes of sm ooth reticulum [Christensen and F awcett, 1966], further confirming that the former are derived from the latter. In addition to acting as a site for the synthetic enzymes involved in the biosynthesis of steroids, the diffuse lipoproteins (or m em branes of agranular endoplasmic reticulum) of steroid gland cells may also accum ulate and store cholesterol as a com ponent of I heir lipids which is now well known to act as the precursor for the biosynthesis of steroid hormones [Guraya, 1968a[Guraya, ,b,c, 1969a[Guraya, , 1971Goodman et al, 1968: Christensen andGii.lim, 1969;Fawcett et al, 1969).…”
Section: Primatesmentioning
confidence: 99%
“….. 277 terized by their content of abundant agranular endoplasm ic reti culum, lipid droplets, m itochondria with tubular cristae, dense bodies, and Golgi apparatus, i.e., similar to cells involved in the production of steroid hormones. Recently, correlated morphological and biochemical studies have shown th at the m em branes of the agranular endoplasmic reticulum (or diffuse lipoproteins) play large roles as sites for enzymes involved in steroidogenesis [see Christen sen , 1965;Christensen and Fawcett, 1966;Goodman et al, 1968;G uraya, 1968a,b,c, 1969aFawcett etal., 1969;Christensen and Gillim, 19691; the Leydig cells of the mouse testis, which contain abundant diffuse lipoproteins (figs.25, 26), also show abundant m em branes of sm ooth reticulum [Christensen and F awcett, 1966], further confirming that the former are derived from the latter. In addition to acting as a site for the synthetic enzymes involved in the biosynthesis of steroids, the diffuse lipoproteins (or m em branes of agranular endoplasmic reticulum) of steroid gland cells may also accum ulate and store cholesterol as a com ponent of I heir lipids which is now well known to act as the precursor for the biosynthesis of steroid hormones [Guraya, 1968a[Guraya, ,b,c, 1969a[Guraya, , 1971Goodman et al, 1968: Christensen andGii.lim, 1969;Fawcett et al, 1969).…”
Section: Primatesmentioning
confidence: 99%
“…1967;Bjersin g , 1967a;P riedkalns and W eb er , 1968;G illim et til.. 1969;Fawcett et ul.. 1968;Goodman et al, 1968: Davies and Broadus, 1908. Similar develop ment of agranular endoplasm ic reticulum in the granulosa cells of the postovulatory follicles has been described recently in the hen [Wyburn el al., 1966] and Amphibia [Kessel and Panje 19681. iii l In-preovulatory and postovulatory follicles of garden lizard ovary 573 Gl'RAYA 11971, 1972a, b, c|, aftei making correlations in the find ings of histochcm ical and electron microscopic studies on the granu losa luteal cells in Mammalia, has suggested that the diffusely distrib uted lipoproteins of histochemical studies derive from the ultrastructural agranular endoplasmic reticulum .…”
Section: Discussionmentioning
confidence: 99%
“…However, Guraya 11971 ] in bis most recent review article has discussed in detail the im portance and physiological significance of diffusely distributed sudanophilic lipoproteins in the granulosa luteal cells as yvell as in other steroidsecreting cells of mammals. Correlated morphological and bio chemical studies have shown th a t the m embranes of agranular endoplasmic reticulum , constituted by the diffusely distributed lipoproteins, play an im portant role as sites for enzymes involved in steroidogenesis [Christensen, 1965;Christensen and Fawcett, 1966;Goodman et «/., 1968Goodman et «/., : F ayvcett et «/.. 1969G uraya, 1971;Christensen and Gillim, 1969]. This is strongly supported by the correlations made in the findings of cytological and histochemical studies by Gi RAYA [1971,1972 a, b, c], which have clearly shown th at the activities of enzymes involved in the biosynthesis of steroid hor mones parallel the presence and developm ent of diffuse lipoproteins (or agranidar endoplasmic reticulum ) in the luteal cells, theca interna cells, and interstitial gland cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1968;Fawcett et al, 1969;Christensen and Gillim, 1969]. It can be assum ed th a t the diffuse lipoproteins dem onstrated histochemically derive from the extensively developed smooth reticulum which acts as a site of enzymes involved in the produc tion of steroid horm ones [Christensen, 1965;Christensen and Fawcett, 1966;Goodman et al, 1968: Fawcett et al, 1969 Chris tensen and Gili.im, 1969]. Histochemical studies have dcm onslraed the presence of various enzymes in the cells of the theca interna, interstitial gland tissue and corpus luteum of rat and ham ster, which are involved in the biosynthesis of steroid hormones | Levy et al, 1959;Taylor, 1961; R ubin et al, 1963 and Balogh.…”
mentioning
confidence: 99%